The Naturals - Barnes, Jennifer Lynn (Barnes, Jennifer (Jennifer Lynn). Naturals novel, 2013)
"Seventeen-year-old Cassie Hobbes is a natural at reading people. Piecing together the tiniest details, she can tell you who you are and what you want. But, it's not a skill that she's ever taken seriously. That is, until the FBI come knocking: they've begun a classified program that uses exceptional teenagers to crack infamous cold cases, and they need Cassie. What Cassie doesn't realize is that there's more at risk than a few unsolved homicides--especially when she's sent to live with a group of teens whose gifts are as unusual as her own. Soon, it becomes clear that no one in the Naturals program is what they seem. And when a new killer strikes, danger looms close. Caught in a lethal game of cat and mouse with a killer, the Naturals are going to have to use all of their gifts just to survive."--